Artisanal fishermen knowledge on the avifauna composition in estuaries from Paraíba State: a contribution for conservation - Araujo, Helder Farias Pereira de; Nishida, Alberto Kioharu (SITIENTIBUS série Ciências Biológicas, 2007)
Studies on animal diversity and ecology provide practical information necessary for the conservation and management of ecosystems, and can indicate contamination pathways as well as environmental transformations. However, avifauna studies in such endangered environments as mangroves are not very common. In an ethnoornithological context, this work has evaluated the knowledge of the local population in relation to the composition of avifauna in estuaries of Paraíba River and Mamanguape River, in state of Paraíba. Ethnobiological methods, together with estimative of species richness methods and comparisons with similarity tests, were used to demonstrate how the avifauna recorded for area was known by local population. Informers have mentioned 94 species of birds. Coefficients of Jaccard and Sorensen, with values of 0.617 and 0.763 respectively, demonstrate a considerable similarity between the composition of the avifauna known by the local population and the one recorded. Distribution of the knowledge was evaluated in relation to the communities’ social aspects. The results and methodology employed have expressed contributions and discussions about practical evaluations for conservation.